Effect Of Mid-Cycle Pgf2α And Gnrh At Ai On Conception Rate, Plasma Progesterone And Biochemical Profile In Repeat Breeding Crossbred Cows - Patel, K.R.; Dhami, A.J.; Hadiya, K.K.; Savalia, K.K.; Killedar, Ankita; Patel , S.B. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
This study was carried out in AMUL milk shed area on 30 crossbred cows, comprising 20 repeat breeding and 10 normal cyclic ones to evaluate their clinical response to mid-cycle PGF2α and AI + GnRH protocol (10 RB cows each) and to monitor plasma progesterone, protein and cholesterol profile at different time intervals post-treatment/AI. Nine out of 10 cows responded within 82.67±4.22 hrs to mid-cycle PGF2α (25 mg, i/m) treatment. The first service and overall conception rates of 3 cycles were 40 and 80 % in mid-cycle PGF2α group; 30 and 70 % in AI + GnRH (20 µg, i/m) group; and 50 and 80 % in normal cyclic control group. The plasma progesterone levels in mid cycle PGF2α protocol on day of treatment, AI and day 21 post-AI were 6.25±1.41, 0.60±0.10 and 9.53±1.66 ng/ml (P
Keywords: Crossbred cows; repeat breeding; controlled breeding techniques; fertility; biochemical profile; plasma progesterone